2022
DOI: 10.3233/shti220525
|View full text |Cite
|
Sign up to set email alerts
|

A Deep Learning Method for Automatic Identification of Drusen and Macular Hole from Optical Coherence Tomography

Abstract: Deep Learning methods have become dominant in various fields of medical imaging, including ophthalmology. In this preliminary study, we investigated a method based on Convolutional Neural Network for the identification of drusen and macular hole from Optical Coherence Tomography scans with the aim to assist ophthalmologists in diagnosing and assessing retinal diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Owing to the paucity of labeled FTMH data, the majority of these models are pre-trained on ImageNet, and subsequently fine-tuned on a small amount of labeled FTMH OCT images. This transfer learning scheme was adopted in developing the classification model by Pace et al [16], which achieves 95% accuracy in distinguishing between normal, Drusen, and FTMH images. Carvalho et al [17], demonstrated an accuracy of 90.6% for FTMH identification, although modeling specifics are not provided.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Owing to the paucity of labeled FTMH data, the majority of these models are pre-trained on ImageNet, and subsequently fine-tuned on a small amount of labeled FTMH OCT images. This transfer learning scheme was adopted in developing the classification model by Pace et al [16], which achieves 95% accuracy in distinguishing between normal, Drusen, and FTMH images. Carvalho et al [17], demonstrated an accuracy of 90.6% for FTMH identification, although modeling specifics are not provided.…”
Section: Introductionmentioning
confidence: 99%
“…The last several years have seen an explosion of deep learning models applied to ophthalmic clinical technologies including OCT and fundus imaging. These applications may be divided into the broad areas of classification/diagnosis [8][9][10][11][12][13][14][15][16][17][18], segmentation [19][20][21][22][23][24][25][26], image quality [27], and demographics prediction [28]. The current ophthalmic deep learning models focus primarily on diabetic retinopathy, age-related macular degeneration, retinopathy of prematurity, and glaucoma [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation